(3GdWYf HGdGSJFfGa ai GdGMcGe GdLfGFjI ai GdbGfhfjfG ddeUQi hGddjHi (B: s (3OQGSI ebGQfI (B/ s - (3SGde YeQ Ydi GdRYdhcs; (3eCehf eMeO SdGeI s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3JfGhdfG ai gPg GdQSGdI GdWYf HGdGSJFfGa ai GdCMcGe GdLfGFjI MjK Je HMK WQb GdWYf ai GdGMcGe hJYQja GdGSJFfGa hPdc ef NdGd KdGK eWGdH bO JfGhdJ ai GdeWdH GdGhd WQb GdWYf ai GdGMcGe GdLfGFjI hai GdeWdH GdKGfi GdGMcGe GdYGeI ddWQb GdWYf ai GdGMcGe hJfGhdJ ai GdKGdK JYQja GdGSJFfGa Ke JfGhdJ HYO Pdc TQhW bHhd GdGSJFfGa hGLQGAGJ GdGSJFfGa hPdc ai GdbGfhf GdeUQi hGddjHis
(3GWQhMI (B((3eGLSJjQ (B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B187-194s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdWYf HGdGSJFfGa ai GdGMcGe GdLfGFjIs; (3GdbGfhf GddjHis; (3GdbGfhf GdeUQis; (3TQhW bHhd GdGSJFfGa s; (3GLQGAGJ GdGSJFfGa s; (3GKGQ GdGSJFfGas; (3GdeMceg GdGSJFfGajg s; (3GdMce HSbhW GdGSJfGa s; (3GdGMcGe GdLfGFjg s; (3GdWYf HGdGSJFfGa s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs